Cytoplasmic DIS3 is an exosome-independent endoribonuclease with catalytic activity toward circular RNAs - Claudia Latini; Julian Eichlinger; Anna-Lisa Fuchs; Si-Nan Zhai; Hung Ho-Xuan; Gerhard Lehmann; Petar Glažar; Nikolaus Rajewsky; Astrid Bruckmann; Li Yang; Remco Sprangers; Gunter Meister (Cell Reports)
Summary: The ribonuclease DIS3 interacts through its PIN domain with the nuclear exosome and degrades linear RNA substrates using its exoribonuclease domain. However, the PIN domain is also an active endoribonuclease, but cellular substrates are largely unknown. Here, we use a biochemical strategy to find ribonucleases that could degrade circular RNAs (circRNAs). Due to the lack of accessible ends, circRNAs are resistant to exonucleolytic cleavage and are thus more stable than linear RNAs. Using biochemical assays, we identify DIS3 as a candidate for circRNA degradation and demonstrate that it partially resides in the cytoplasm, where circRNAs are degraded. DIS3 shows cleavage activity toward a number of circRNAs and functions independently of the exosome core in vitro. Upon knockdown of DIS3 in cell lines, selected circRNAs are moderately stabilized. We thus propose that cytoplasmic DIS3 functions as a stand-alone enzyme independently of the exosome core and may contribute to circRNA turnover.